2008
DOI: 10.1016/s0091-679x(08)85007-8
|View full text |Cite
|
Sign up to set email alerts
|

Counting Kinetochore Protein Numbers in Budding Yeast Using Genetically Encoded Fluorescent Proteins

Abstract: Genetically encoded fluorescent proteins are an essential tool in cell biology, widely used for investigating cellular processes with molecular specificity. Direct uses of fluorescent proteins include studies of the in vivo cellular localization and dynamics of a protein, as well as measurement of its in vivo concentration. In this chapter, we focus on the use of genetically encoded fluorescent protein as an accurate reporter of in vivo protein numbers. Using the challenge of counting the number of copies of k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 55 publications
(60 reference statements)
4
77
0
Order By: Relevance
“…In histograms of fluorescence intensities, we observed a trail in the distribution toward higher fluorescence intensities that might indicate formation of complexes with more subunits (see Supplemental Figure 1, A-F). To confirm these conclusion, we also GFP-tagged kinetochore proteins Cse4 and Spc105 as markers to quantify in vivo protein numbers (Joglekar et al, 2008). One kinetochore cluster of Cse4-GFP represents the fluorescence of 32 GFP molecules, whereas a kinetochore cluster of Spc105-GFP represents 80 GFP molecules.…”
Section: All Torc2 Components Localize As Oligomeric Foci To the Plasmentioning
confidence: 86%
“…In histograms of fluorescence intensities, we observed a trail in the distribution toward higher fluorescence intensities that might indicate formation of complexes with more subunits (see Supplemental Figure 1, A-F). To confirm these conclusion, we also GFP-tagged kinetochore proteins Cse4 and Spc105 as markers to quantify in vivo protein numbers (Joglekar et al, 2008). One kinetochore cluster of Cse4-GFP represents the fluorescence of 32 GFP molecules, whereas a kinetochore cluster of Spc105-GFP represents 80 GFP molecules.…”
Section: All Torc2 Components Localize As Oligomeric Foci To the Plasmentioning
confidence: 86%
“…However, possible interference of the fluorescent tag with protein function remains a concern. In addition, quantitative measurements of fluorescence signals are complicated by photo‐bleaching, quenching of signal intensity, and the difficulty of dependable standardization (Joglekar et al , 2008; Lawrimore et al , 2011; Coffman & Wu, 2012). Thus, we are reassured by the good concordance between results obtained through use of the two complementary approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Structural analysis in vitro has shown that a Dam1 ring contains at least 16 copies of the complex (5,6). To test whether SpDam1 forms rings around MTs, we measured the copy number of Dam1 in individual spots on cytoplasmic MTs, using an established quantitative fluorescence microscopy approach (18,25,27). We examined strains expressing tri or di-GFP-tagged Dam1 complexes, and deduced the copy number of Dam1 ( Fig S2 and Materials and Methods).…”
Section: Identification Of Discrete Dam1 Assemblies On Cytoplasmic Mtmentioning
confidence: 99%